Between judging and listening: sexuality and abortion in a low-income neighborhood - Tornquist, Carmen Susana; Miguel, Denise Soares; Assis, Gláucia de Oliveira (FCL-UNESP Laboratório Editorial, 2012)
In this article we analyze some of the representations of abortion among the dwellers of a low-income neighborhood in Florianópolis by focusing on interviews with women and speeches from prominent female in the community, such as health agents and community leaders. Several methodologies were used in this research. It was observed that the abortive history is characterized by a specific temporality, which includes the participation of other women and in which the abortive traditional processes are combined with the use of misoprostol (Cytotec). The kind of substance and the usage of these different methods indicate significant differences between the process of “testing or forcing the blood out” and the abortion itself. Such differences are also moral. Although in this neighborhood the condemnatory discourses against abortion may prevail (except in situations involving victims of rape), it was also observed, especially when dealing with concrete cases, a more condescending attitude towards women who decide for having an abortion. Such condescendence is summarized in the statement: “I´d rather not judge”.